Diastereoselective Reduction of β-(1,3-Dioxan-4-yl)ketones - Matsumoto, Akira; Asano, Keisuke; Matsubara, Seijiro (Synlett, 2015)
Stereoselective reduction of β-(1,3-dioxan-4-yl)ketones is an important step in the efficient synthesis of chiral 1,3-polyols, a typical structure of polyketides. In this study, we carried out investigations to optimize the conditions for diastereoselective reduction.
Keywords: diastereoselective reduction; chiral acetal; 1,3-dioxane; 1,3-polyol; polyketide